IMPLEMENTASI PROTOKOL KESEHATAN OLEH MAHASISWA DI KOTA MALANG SELAMA GELOMBANG KE-2 COVID-19: PERIODE JULI-AGUSTUS 2021 - Edi Suriaman Suriaman; Nugroho Tristyanto; Miftakhul Mujahidin; Herlina Alfianti; Tin Ni’am; Annisa Qoyumi Hartanti; Adellia Puspita Ningrum (Politeknik Medica Farma Husada Mataram, 2023)
The second wave of COVID-19 infection spread has occurred in Indonesia. There has been an increase in COVID-19 cases in various provinces in Indonesia based on a June 2021 report. This should encourage every community group, especially students, to be more strict in carrying out health protocols. The study used a questionnaire (google form) to collect data with a number of questions as many as 15 items. Sampling techniques are accidental sampling. Data is done validation and reliability test, then the difficulty is analyzed using a univariate test. During the 2nd wave of COVID-19, the government imposed restrictions on community activities in Malang City. During this time, students are increasingly aware of implementing health protocols by government advice. The percentage of respondents who kept their distance (91%), washed their hands, and used hand sanitizer (92.6%) during the 2nd wave of COVID-19 was very high. Respondent's interest in participating in vaccination programs is very high at 85.3%. Some other positive activities are also carried out to increase immunity such as taking vitamins (75.5%), as well as exercise and sunbathing (70.5%). The discipline of implementing health protocols will reduce the potential for the emergence of the third wave of COVID-19 in Indonesia.